Melatonin Alleviates Cardiac Function in Sepsis-Caused Myocarditis via Maintenance of Mitochondrial Function - Chen, Liyang; Tian, Qing; Shi, Zhiguang; Qiu, Yu; Lu, Qiulun; Liu, Chao (Frontiers in Nutrition, 2021)
Melatonin (N-acetyl-5-methoxytryptamine) has been shown to have a cardioprotective effect against myocarditis. However, the mechanisms underlying the protective role of melatonin (MLT) in sepsis-induced myocarditis are yet to be revealed. In this study, MLT was administrated to mice, 14 days before cecal ligation puncture surgery. Echocardiography results showed that MLT alleviated cardiac dysfunction in sepsis-induced myocarditis. Furthermore, MLT reduced cardiac inflammation by inhibiting the expression of Il-1α, Il-1β, Il-6, and Mcp-1 messenger RNA (mRNA) levels. The RNA sequencing (RNA-seq) assays with heart tissues showed that MLT maintains the mitochondrial function in sepsis-caused myocarditis. Additionally, the production of reactive oxygen species (ROS) in heart tissues was suppressed by MLT. Taken together, in evaluating the therapeutic effect of MLT on sepsis-induced myocarditis, the results showed that MLT alleviated cardiac damage by regulating mitochondrial function and mitochondrial ROS.